1992
DOI: 10.1139/g92-098
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DNA methylation on rye B-chromosome nondisjunction

Abstract: Regulation of nondisjunction of the rye B chromosome was investigated using the cytidine analog 5-azacytidine, which affects DNA methylation. The B chromosome of rye normally undergoes nondisjunction at first pollen grain mitosis and is stable at all other mitotic nuclear divisions. Observations on mitosis in the control root cells showed normal chromosome behaviour, whereas the treated roots were characterized by a high frequency of anaphases with lagging chromosomes showing evidence of failure of chromatid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…5-Azacytidine has also been reported to alter DNA replication patterns and disturb the cell cycle (34,35). Finally, 5-azacytidine has been reported to cause nondisjunction of B chromosomes in rye (36). The availability of a collection of methylation mutants in a model eukaryote will allow us to examine directly the possible ties between DNA methylation and important functions of the chromosome, including replication, segregation, and gene expression.…”
mentioning
confidence: 99%
“…5-Azacytidine has also been reported to alter DNA replication patterns and disturb the cell cycle (34,35). Finally, 5-azacytidine has been reported to cause nondisjunction of B chromosomes in rye (36). The availability of a collection of methylation mutants in a model eukaryote will allow us to examine directly the possible ties between DNA methylation and important functions of the chromosome, including replication, segregation, and gene expression.…”
mentioning
confidence: 99%
“…It is known that both in animals and in plants some DNA methylation patterns are modified during meiosis (Holliday 1987, Monk 1987, Neves et al 1992. We suggested that nucleolar dominance in triticale could also be reprogrammed in meiosis through the alteration of rDNA methylation patterns established in somatic cells during early stages of seed development (Castilho et al 1995).…”
Section: Introductionmentioning
confidence: 91%
“…In addition to e¡ects on transcription, non-Mendelian B-chromosome behaviour may also be in£uenced by methylation. Neves et al (1992) showed that induced demethylation (or blocking of methylation) in rye (Secale cerale) causes B chromosomes to undergo mitotic non-disjunction, a known B-chromosome accumulation mechanism.…”
Section: (D) Epigenetic Changes In B Chromosomesmentioning
confidence: 99%